Computational Associative Memory with Amorphous Metal‐Oxide Channel 3D NAND‐Compatible Floating‐Gate Transistors (Adv. Electron. Mater. 12/2022). (9th December 2022) - Sun, Chen; Li, Chao; Samanta, Subhranu; Han, Kaizhen; Zheng, Zijie; Zhang, Jishen; Kong, Qiwen; Xu, Haiwen; Zhou, Zuopu; Chen, Yue; Zhuo, Cheng; Ni, Kai; et al.
Abstract : Massively Scalable Ternary Content‐Addressable Memories In article number 2200643, Xunzhao Yin, Xiao Gong, and co‐workers present high‐performance floating‐gate transistors with an amorphous‐InGaZnO channel and the application in ternary content addressable memories (TCAMs). The two‐transistor configuration and the extremely low OFF current of the TCAM cell significantly improve the scalability of the TCAM array.